Facility planning and design for health, physical activity, recreation, and sport - Sawyer, Thomas H. (Sagamore-Venture, 2019)
As the cost of construction for sports and health-related facilities skyrockets, it becomes paramount for those who plan, design, construct, and use these facilities to have access to a comprehensive facilities guide. The 14th edition of Facility Planning and Design for Health, Physical Activity, Recreation, and Sport is a tool for all professionals involved in facility planning and construction use